NEW ONSET GRAVES’ DISEASE AFTER SARS-CoV-2 VACCINATION - Seng, Chiew Ken; Wei, Lee Ling; Hui, Khaw Chong (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION There is an increasing number of reports of thyroid dysfunction after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. We would like to report a case of new onset Graves’ disease following vaccination with the adenovirus-vectored Vaxzevria (Oxford-AstraZeneca). METHODOLOGY A 29-year-old lady with no prior history of endocrine or autoimmune diseases, presented with a week of palpitations, heat intolerance and excessive sweating three days after her second dose of Vaxzevria. She did not experience these symptoms after her first dose which she received two months earlier. Her father and sister have Graves’ disease. She had a diffuse goiter with no orbitopathy. Thyroid Stimulating Hormone (TSH) was <0.01 mIU/L (normal range: 0.27-4.2) with a markedly elevated free T4 of >100 pmol/L (normal range: 12-22). TSH receptor antibody was positive at >40.00 IU/L (Normal range: <1.75). Ultrasonography revealed a hypervascular, diffusely enlarged goiter. She was started on oral carbimazole and propranolol. Five months later, her free T4 had normalized at 18 pmol/L though her TSH was still undetectable. To date, she remains hesitant for her booster dose. RESULTS SARS-CoV-2 infection and vaccination have been associated with subacute thyroiditis and autoimmune thyroid disease. While there are reports of new onset Graves’ disease after mRNA and adenovirus-vectored vaccines, it has not been associated with inactivated virus vaccines. The current prevailing theory is that the adjuvants in the vaccines can trigger an autoimmune event, also called “autoimmune/inflammatory syndrome induced by adjuvants” (ASIA). CONCLUSION Physicians need to be aware of thyroid dysfunction after SARS-CoV-2 vaccination, especially in those with a strong family history of autoimmune disease. Nevertheless, it is also important to note that the benefit of vaccination far outweighs this uncommon potential risk. More studies are required to establish a causal relationship.